2018
DOI: 10.1186/s13046-018-0935-8
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin specifically aggravates ER stress and overcomes chemoresistance in multidrug-resistant gastric cancer cells by inhibiting N-glycosylation

Abstract: BackgroundMultidrug resistance remains a major obstacle to successful treatment for patients with gastric cancer (GC). Recently, glycosylation has been demonstrated to play a vital role in the acquisition of multidrug resistance. As a potent inhibitor of glycosylation, tunicamycin (Tu) has shown marked antitumor activities in various cancers. In the present study, we attempted to determine the exact effect of Tu on the chemoresistance of GC.MethodsThe cytotoxic effects of drugs on GC cells were evaluated by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 63 publications
7
112
0
1
Order By: Relevance
“…Furthermore, some analysis revealed ATGs were differentially enriched in platinum resistance. Research has demonstrated that a combination of inhibitors in GC improves cisplatin resistance [26][27][28] , which is consistent and concurs with our results. ATGs can promote progress in GC disease progress through platinum resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, some analysis revealed ATGs were differentially enriched in platinum resistance. Research has demonstrated that a combination of inhibitors in GC improves cisplatin resistance [26][27][28] , which is consistent and concurs with our results. ATGs can promote progress in GC disease progress through platinum resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Both activating and inhibiting ER stress can overcome chemoresistance and radioresistance in cancer [70][71][72]. This indicates that the roles of ER stress in cell fate are multifaceted and context-dependent.…”
Section: Remodeling Of Er Stress Autophagy and Phagocytosismentioning
confidence: 99%
“…5c), suggesting that ER stress induction also regulates the PPARγ expression. To con rm the mechanism that ER stress induction kills bladder cancer cells, we then treated the cells with the ER stress inducer tunicamycin [41].…”
Section: Pparγ Activation Played a Pivotal Role In Killing Bladder Camentioning
confidence: 99%